2016
DOI: 10.1590/s1980-6574201600030009
|View full text |Cite
|
Sign up to set email alerts
|

Teacher efficacy beliefs during the practicum experiences in physical education classes

Abstract: Abstract--Previous studies focusing on teacher education have highlighted the role that supervised practicum plays in the construction of future teachers' personal beliefs, including self-efficacy beliefs, yet there remains a need to understand which learning experiences contribute to the constitution of this belief during the supervised practicum. Our objective was to identify situations that influenced student teachers' judgment of self-efficacy during the development of supervised practicum. This explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
0
17
0
4
Order By: Relevance
“…These seem to be important to provide confidence and motivation for the beginning teachers. Although the literature acknowledges the supervised practicum as the central locus of the initial training (Aydin et al, 2012), studies under the theoretical perspective adopted for this study are still novel, especially with undergraduates and physical education teachers early in their careers (Hand & Stuart, 2012;Iaochite & Costa Filho, 2016). This reinforces the need to increase the investigation towards this direction.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These seem to be important to provide confidence and motivation for the beginning teachers. Although the literature acknowledges the supervised practicum as the central locus of the initial training (Aydin et al, 2012), studies under the theoretical perspective adopted for this study are still novel, especially with undergraduates and physical education teachers early in their careers (Hand & Stuart, 2012;Iaochite & Costa Filho, 2016). This reinforces the need to increase the investigation towards this direction.…”
Section: Discussionmentioning
confidence: 93%
“…For example, in the specific domain of teaching physical education, research results present that undergoing supervised practicum programs during the initial education have brought valuable educational experiences for the constitution of self-efficacy. From these, the opportunity of a contextualized teaching, especially in terms of infrastructure and school community (Iaochite & Costa Filho, 2016) and the observation of school teachers teaching (Zach, Harari, & Harari, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows a moderate correlation between the vicarious source and the perceived TSE level. A study by Iaochite and Costa Filho 25 with reflective portfolios applied to 18 university students during the mandatory internship period of a public university in São Paulo, Brazil, showed that the observation of teaching situations in different contexts, as well as the observation of their peers teaching in internships, allowed the university students to find support to solve problems and deal with adverse situations in teaching.…”
Section: Discussionmentioning
confidence: 99%
“…In the initial teacher training for Physical Education, studies have also indicated that the main source of TSE for university students is direct experience, especially during the mandatory internship 5,14,27,34 . For Iaochite and Costa Filho 25 , it is through direct interventions related to teaching during the mandatory internship that the university students studying Physical Education can acquire significant experiences for their training, stimulating the reflection of their capacities to teach and mobilize knowledge originating from their initial training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation